Pulmonary Onset of Adult Onset Still’s Disease Complicated with Kikuchi Lymphadenitis - G. D. E. Kodithuwakku; C. L. Fonseka; S. Nanayakkara; H. M. M. Herath (Case Reports in Rheumatology)
Background. Adult onset Still’s disease (AOSD) is a rare inflammatory disorder with a variety of clinical presentations. Even though pneumonitis and pleurisy are known to occur in AOSD, pulmonary onset presentations are exceedingly rare. Case Presentation. We present a 40-year-old male, presenting with fever and bilateral alveolar shadows with pleural effusions mimicking community-acquired severe pneumonia. He was initially treated as severe pneumonia with poor response to broad spectrum antibiotics. Subsequently, he was managed as AOSD-induced pneumonitis, as he fulfilled Yamaguchi criteria. Few weeks later, he developed macular rash and arthralgia with generalized lymphadenopathy with lymph node histology, showing Kikuchi lymphadenitis. He responded well to steroids and had a complete recovery. Conclusion. Non-infective causes of pneumonitis should be suspected in the setting of poorly resolving pneumonias, especially when microbiological and serological investigations does not support an infective etiology. Presence of systemic symptoms with arthralgia, rash, and disproportionately elevated ferritin level supports the diagnosis of AOSD. Kikuchi lymphadenitis is a reported association with AOSD, and there could be a causal link between the two disorders.